Counseling on Worms and Scabies for Teenagers in Karang Tengah Village, Gunung Pancar - Langi, Louisa Ariantje; Tandilangi, Glorya Yolanda; Susanto, Jason Daniel; Beding, Beatrix Melanie; Sanggul, Andriyani Risma (International Journal of Community Service (IJCS), 2025)
Background: Worms and scabies are two common health problems found in areas with inadequate sanitation, including rural areas such as Karang Tengah Village, Gunung Pancar. Adolescents are a vulnerable group to these two diseases due to suboptimal hygiene practices and limited health knowledge. Objective: This activity aims to increase adolescents' understanding of the transmission, symptoms, prevention, and initial management of worms and scabies through interactive counseling activities. Method: The activity was carried out in the form of counseling with a participatory approach in the village hall, involving 45 adolescents aged 12–18 years. The material was provided through presentations, discussions, and the distribution of educational leaflets. Evaluation was carried out with a pretest and posttest to measure changes in knowledge. Results: There was a significant increase in knowledge after the counseling, with an average pretest score of 56.2 increasing to 84.5 in the posttest. In addition, participants showed high enthusiasm and expressed a commitment to implementing clean and healthy living behaviors. Conclusion: Health counseling has been proven effective in increasing adolescents' understanding of worms and scabies. Educational interventions such as these are recommended to be implemented periodically in similar communities to prevent the occurrence of environmentally based infectious diseases.